Egyptian presidents' speeches in times of crisis: Comparative analysis - Abdel Fattah, Dina Tawfic (AUC Knowledge Fountain, 2015)
The political speech is a bridge between politicians and the public, with most politicians seek to gain the public’s support and persuade them with their policies. In the modern era, the political speech becomes a crucial tool of Presidents’ communication with the public, particularly during domestic or international strife. Previous literature highlighted the political speeches of foreign Presidents in the U.S., Indonesia, and UK, with few studies analyzed the Arab political speeches. This study fills the gap by presenting a critique of the speeches given by three Egyptian Presidents during periods of crisis. Crisis in that context refer to "events of profound significance and disruption" (Hicks, 2005, p1). The current study analyzes the following speeches: Hosni Mubarak's "25th Revolution,"(2011) Mohamed Morsi's "One Year Accountability"(2013), and Abdel Fattah El Sisi's "Sinai attacks" (2015). The three speeches were downloaded from YouTube, and then transcribed into Arabic texts. Two approaches of critical discourse analysis (CDA) are used, along with positioning theory, to reveal discourse strategies in the three presidential speeches. The two approaches of CDA are: Fairclough approach (1989) and Discourse- Historical approach (Resigl & Wodak, 2009). The Findings show that the three Egyptian Presidents use similar discourse strategies during the times of crises despite the differences in the socio-political contexts. Inclusiveness, conspiracy rhetoric and the involvement of foreign elements, memorizing Presidents’ achievements, and emotional approach were among the most common strategies used by the three Egyptian Presidents in the selected speeches.